2021
DOI: 10.3390/su132011513
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Social Entrepreneurs in Southeast Europe: GEM Data Analysis

Abstract: With this paper, we aim to examine the relationship between cognitive, social, and demographical factors, as well as national culture and its relationship with social entrepreneurial activity in Southeast Europe (SEE). The empirical research employs a binary logistic regression model, utilizing data obtained from the Global Entrepreneurship Monitor. For the purpose of the empirical research, we selected a sample of early-stage entrepreneurs who founded their businesses in Hungary, Romania, Slovenia, Croatia, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…Urbano & Alvarez [42] found a positive relationship between media attention and entrepreneurial intention. Leković et al [43] observed a positive relationship between entrepreneurship solving social problems and entrepreneurial intention, resonating with SDG 11 (Sustainable Cities and Communities), but a negative association with media coverage of new business success. Ferri et al [44] noted that the social image of entrepreneurship positively correlates with social entrepreneurship in times of financial crisis, supporting SDG 1 (No Poverty).…”
Section: Social Values Towards Entrepreneurship and Entrepreneurial I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Urbano & Alvarez [42] found a positive relationship between media attention and entrepreneurial intention. Leković et al [43] observed a positive relationship between entrepreneurship solving social problems and entrepreneurial intention, resonating with SDG 11 (Sustainable Cities and Communities), but a negative association with media coverage of new business success. Ferri et al [44] noted that the social image of entrepreneurship positively correlates with social entrepreneurship in times of financial crisis, supporting SDG 1 (No Poverty).…”
Section: Social Values Towards Entrepreneurship and Entrepreneurial I...mentioning
confidence: 99%
“…Established in 1997, the GEM's overarching mission is to foster global development through the comprehensive measurement and analysis of various facets related to entrepreneurship. In particular, the GEM's extensive database on entrepreneurial intentions has been a valuable resource for secondary data in numerous scholarly studies, including those by Leković et al [43], Linardi and Costa [81], Pita et al [82], Ratten et al [59], Urbano and Alvarez [42], and Voda et al [83]. Recognizing that the randomness of the sample is crucial for its validity and representativeness, the Global Entrepreneurship Monitor (GEM) Adult Population Survey (APS) employs a stratified probabilistic sampling technique, ensuring that each individual within the defined strata has an equal and known chance of being selected, thus accurately reflecting the diversity and characteristics of the adult population in each country studied.…”
Section: Data and Samplementioning
confidence: 99%
“…Logistic regression is defined as a classical statistical model, which is used to analyze the relationship between a dichotomous or binary dependent and one or more nominal, ordinal, interval, or ratio-level independent variables [140]. Logistic regression is also referred to as logit model, which is widely applied in the field of entrepreneurship [141,142]. Based on the logit transformation of the dependent variable, logistic regression model could quantify the occurrence "odds" of an event and predict the outcome probabilities for dependent variable [143].…”
Section: Empirical Strategymentioning
confidence: 99%
“…Despite having many similarities, social ventures are different in acquiring resources. If facing sustainability issues, social entrepreneurs face more challenges in taking advances from financial institution and are more reluctant to provide advances or credit (Lekovic et al, 2021).…”
Section: Social Entrepreneurship (Se) and Commercial Entrepreneurship...mentioning
confidence: 99%